2017
DOI: 10.1111/ijd.13736
|View full text |Cite
|
Sign up to set email alerts
|

Failure of initial disease control in bullous pemphigoid: a retrospective study of hospitalized patients in a single tertiary center

Abstract: The low frequency of recalcitrant BP (6.1%) and the rarity of involvement of the oral mucosa (1.8%) in this study suggest that Israeli BP patients present a milder phenotype compared to similar patients from other geographic areas. Hypertension, head involvement, and metformin therapy were found to be significantly associated with the need for adjuvant therapy to achieve initial control, suggesting that these parameters may serve as predictors of treatment response in BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Our results were consistent with recently published studies carried out by Kremer et al, who found that arterial hypertension was the most frequent comorbidity in BP (in 64% of patients studied, p = 0.04). 21 In studies by Kwan et al and Cai et al, arterial hypertension was also the most frequent out of all comorbidities (in 62.8% and 59.3%, respectively). 13,20 In another study concerning BP patients, multi-morbidity was observed in 84% with the highest percentage for arterial hypertension.…”
Section: Association With Cardiovascular Diseasesmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results were consistent with recently published studies carried out by Kremer et al, who found that arterial hypertension was the most frequent comorbidity in BP (in 64% of patients studied, p = 0.04). 21 In studies by Kwan et al and Cai et al, arterial hypertension was also the most frequent out of all comorbidities (in 62.8% and 59.3%, respectively). 13,20 In another study concerning BP patients, multi-morbidity was observed in 84% with the highest percentage for arterial hypertension.…”
Section: Association With Cardiovascular Diseasesmentioning
confidence: 92%
“…The fact is that this disease may play an important role in BP patients, especially since major drugs used to treat hypertension such as diuretics, ACE inhibitors or spironolactone can provoke BP. 6,13,[20][21][22] Among other comorbidities, single studies have demonstrated the association of BP with diabetes. [23][24][25] To confirm or reject the abovementioned discrepancies, the aim of this study was to assess the relationship between BP and selected comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, cardiovascular diseases result the most frequent comorbidities (70%), followed by CNS disorders (37%), type 2 diabetes (15%) and malignant tumors (14%) (5). In their study, Kremer et al have shown that arterial hypertension was the most frequent comorbidity in patients with BP (64% of patients, p=0.04) (6). Conversely, the use of some antihypertensive drugs (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…For this disease, we found nine case series (36,48,63,(99)(100)(101)(102)(103)(104) of which two were prospective. In total 249 patients were enrolled.…”
Section: Bullous Pemphigoid (Bp)mentioning
confidence: 99%